2000
DOI: 10.1136/thorax.55.6.459
|View full text |Cite
|
Sign up to set email alerts
|

TGF-beta 1 genotype and accelerated decline in lung function of patients with cystic fibrosis

Abstract: Background-Polymorphisms in transforming growth factor (TGF)-1 associated with variations in cytokine levels are linked to fibrosis in a number of tissues. However, the contribution of this cytokine to organ fibrosis in patients with cystic fibrosis is presently unclear. This study was undertaken to examine the association between TGF-1 gene polymorphisms and the development of pulmonary dysfunction in patients with cystic fibrosis. Methods-Polymorphisms in the TGF-1 gene defining amino acids of codons 10 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
140
2
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 16 publications
(12 reference statements)
9
140
2
7
Order By: Relevance
“…In humans, whether healthy people with increased CXCL8, CCL2, or TGF-β1 blood concentrations are specifically at risk for development of fibrosis has not been studied. Nevertheless, some studies highlighted the fact that IPF patients with a high TGF-β1 producing genotype are incline to have a worse prognosis and a more rapid deterioration in lung function (Arkwright et al, 2000;Alhamad et al, 2013). A single nucleotide polymorphism (rs4073T N A) was also recently found in the promoter of the CXCL8 gene and was significantly associated with higher BALF CXCL8 concentrations and an increased risk of development of IPF in humans (Ahn et al, 2011).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…In humans, whether healthy people with increased CXCL8, CCL2, or TGF-β1 blood concentrations are specifically at risk for development of fibrosis has not been studied. Nevertheless, some studies highlighted the fact that IPF patients with a high TGF-β1 producing genotype are incline to have a worse prognosis and a more rapid deterioration in lung function (Arkwright et al, 2000;Alhamad et al, 2013). A single nucleotide polymorphism (rs4073T N A) was also recently found in the promoter of the CXCL8 gene and was significantly associated with higher BALF CXCL8 concentrations and an increased risk of development of IPF in humans (Ahn et al, 2011).…”
Section: Cxcl8 and Ccl2 Concentrationsmentioning
confidence: 99%
“…12,13 A case-control study involving 1306 participants found that the TT genotype at TGFβ1 position −509 was associated with more severe lung disease. 13 Our results demonstrated that secondhand smoke exposure was associated with a 22.7 percentile point decrease in cross-sectional lung function in patients with the TT genotype exposed to secondhand smoke compared with nonexposed TT homozygotes.…”
Section: Commentmentioning
confidence: 99%
“…TGFβ1 was selected for study because genotypic variants of TGFβ1 have been shown to modify the severity of CF [11][12][13] and the development and/or severity of other chronic respiratory tract conditions, including asthma [14][15][16][17][18] and chronic obstructive pulmonary disease. [19][20][21] …”
mentioning
confidence: 99%
“…7 Several polymorphisms have been described for the TGF-b 1 gene. [17][18][19][20] The polymorphism (G-C) located within exon 1 at codon 25 (915 bp downstream of the start point) is associated with decreased production of TGF-b 1 in vitro (C allele). This polymorphism is associated with an increased frequency of lung fibrosis and a more rapid decline of lung function in patients with cystic fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism is associated with an increased frequency of lung fibrosis and a more rapid decline of lung function in patients with cystic fibrosis. [17][18][19][20] Recruitment of mononuclear cells to the lung and their subsequent activation is an important pathological feature of lung fibrosis and is regulated by chemotactic cytokines such as monocytes chemoattractant protein-1 (MCP-1). 21 MCP-1 has been implicated in the pathogenesis of chronic inflammatory lung diseases that have a fibrotic component.…”
Section: Introductionmentioning
confidence: 99%